2006
DOI: 10.1542/peds.2005-1414
|View full text |Cite
|
Sign up to set email alerts
|

Familial and Genetic Susceptibility to Major Neonatal Morbidities in Preterm Twins

Abstract: Twin analyses show that intraventricular hemorrhage, necrotizing enterocolitis, and bronchopulmonary dysplasia are familial in origin. These data demonstrate, for the first time, the significant genetic susceptibility for bronchopulmonary dysplasia in preterm infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
198
2
6

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(209 citation statements)
references
References 27 publications
3
198
2
6
Order By: Relevance
“…While changes in ventilation management could potentially impact in the 26 to 28 weeks GA category of infants, for the smallest group, especially with the advent of 'new' BPD, genetic approaches should be paramount. 38 With the current explosion of genomic techniques and decreasing cost, this is now a viable option.…”
Section: Characteristics Of Infants With Bpdmentioning
confidence: 99%
“…While changes in ventilation management could potentially impact in the 26 to 28 weeks GA category of infants, for the smallest group, especially with the advent of 'new' BPD, genetic approaches should be paramount. 38 With the current explosion of genomic techniques and decreasing cost, this is now a viable option.…”
Section: Characteristics Of Infants With Bpdmentioning
confidence: 99%
“…Environmental factors, such as high levels of oxygen exposure, mechanical ventilation, or repeated infections play a major role in etiology, although recent studies have suggested an important genetic predisposition. 1 Infants with BPD are at increased risk of death, childhood respiratory complications and long-term neurodevelopmental problems. 2,3 The lack of sustained clinical benefits from late postnatal therapeutic interventions and the undesirable harmful effects of post-natal corticosteroids have fueled interest in seeking early biological markers useful in targeting therapeutic interventions aimed at promoting long-term pulmonary and neurodevelopmental benefits.…”
Section: Introductionmentioning
confidence: 99%
“…2,5,6 Sepsis in utero, in addition to ventilator-induced injury and hyperoxia, initiates an inflammatory cascade, which acts on the immature lungs. 2 Inflammation interferes with the normal development of airways and alveoli, and abnormal healing in the premature infant further exacerbates lung damage, resulting in BPD.…”
Section: Introductionmentioning
confidence: 99%